The Role of Hadith in The Formation of a Healthy Lifestyle of Adolescents (Texas Journal of Multidisciplinary Studies, 2023)
The goal of modern education is to increase attention to the use of Hadith in the formation of a healthy lifestyle, and in educating young people to instill respect for national and global values, to develop a sense of patriotism, hygienic, cultural, physical, aesthetic education and hard work. Since ancient times, our ancestors have sought to create a strong family, raising a healthy and perfect generation. Various social factors contribute to the formation of universal human values, the concept of the religion of Islam, in the minds of our children. There is a powerful tool against the spread in society of radical views, extremist and terroristic ideas that poison the minds of young people. These are such nationalreligious values as humaneness, peacefulness, love for enlightenment and creation.